2021
DOI: 10.3389/fgene.2021.697524
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Ferroptosis-Related Gene Signature and Nomogram for Predicting the Prognosis of Esophageal Squamous Cell Carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is a common malignant tumor with high mortality and poor prognosis. Ferroptosis is a newly discovered form of cell death induced by iron-catalyzed excessive peroxidation of polyunsaturated fatty acids (PUFAs). However, the prognostic value of ferroptosis-related genes (FRGs) for ESCC remains unclear. Based on the ESCC dataset from the Gene Expression Omnibus (GEO) database, we identified 39 prognostic FRGs through univariate Cox regression analysis. After LASSO regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…NAD(P)H: ubiquinone oxidoreductase-1 (NQO1) functioned as a CoQ oxidoreductase and mitochondrial ROS inhibitor and has been demonstrated to suppress ferroptosis ( Sun et al, 2016 ; Peng et al, 2022 ). Studies have shown that the activation of SRC proto-oncogene non-receptor tyrosine kinase (SRC) can inhibit cancer cell ferroptosis by inhibiting the expression of acyl-CoA synthetase long-chain family member 4 (ACSL4) ( Brown et al, 2017 ; Ye et al, 2021 ). This further suggested the regulatory role of LINC02432/hsa-miR-98–5p/HK2 axis on ferroptosis inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…NAD(P)H: ubiquinone oxidoreductase-1 (NQO1) functioned as a CoQ oxidoreductase and mitochondrial ROS inhibitor and has been demonstrated to suppress ferroptosis ( Sun et al, 2016 ; Peng et al, 2022 ). Studies have shown that the activation of SRC proto-oncogene non-receptor tyrosine kinase (SRC) can inhibit cancer cell ferroptosis by inhibiting the expression of acyl-CoA synthetase long-chain family member 4 (ACSL4) ( Brown et al, 2017 ; Ye et al, 2021 ). This further suggested the regulatory role of LINC02432/hsa-miR-98–5p/HK2 axis on ferroptosis inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, the researcher selected SLC38A1 with noticeable expression difference to further explore its influence on the proliferation and migration of ESCC cells and finally concluded that SLC38A1 promoted the proliferation and migration of ESCC cells ( Song et al, 2021 ); Ye et al identified SRC, FADS2, GLUD1, POLG, ANO6, SLC2A6, PTGS2, ALOXE3, etc. ( Ye et al, 2021 ); Zhao et al identified six FRGs with prognostic value in 112 ESCC samples ( Zhao M. et al, 2022 ). Among them, the expressions of PRNP, SLC3A2, SLC39A8, and SLC39A14 were negatively correlated with the prognosis of ESCC patients, while the expressions of ATP6V0A1 and LCN2 were the opposite.…”
Section: Study On Ferroptosis In Esophageal Cancermentioning
confidence: 99%
“…However, this eld of study has not seen signi cant progress in esophageal cancer, largely due to insu ciencies in data sets. In existing studies, researchers have utilized multiple datasets and examined genes associated with signal pathways, including ferroptosis [6,7] , epithelial-mesenchymal transition [8], and autophagy-related genes [9]. Nevertheless, due to various factors such as lack of data sets, inferior quality of data sets, and incompleteness of research schemes, the established gene signatures have not shown substantive discriminative capability in prognosticating for ESCC patients, with AUC values often distributed around 0.7.…”
Section: Introductionmentioning
confidence: 99%